Analisis Tingkat Pengetahuan Peternak Domba dengan Menggunakan Uji T dan Wilcoxon di Kelompok Tani Tani Maju - Hastari, Bismi Widi; Gandasari, Dyah; Harry, Harry (Politeknik Pembangunan Pertanian Bogor, 2020)
Tani Maju farmer group is one of the farming groups located in Rorotan Village, Cilincing District, North Jakarta City Administration. This group has a lot of sheep and advanced management. Despite they manage their sheep well, they are not well informed on how to manage the sewage from their castles (faces and urine). So far, they just throw away the sewage or gave them to fellow farmers. This study aimed to analyze the level of farmers' knowledge in making use of sheep's urine to be degraded into bio urine in the Maju Farmer group. Data was collected through the pre-test and post-test. The data were analyzed using paired t-test and Wilcoxon statistical software (IBM SPSS Statistics 25). The results of the study showed that farmers' knowledge in sewage (Urine) management increased; there is a significant difference in farmers' level of knowledge in bio urine production before and after bio urine extension.